Analysis of Learning Difficulties in Elementary School Students in Jean Piaget's View - Najwa Rihadatul 'Aisy; Valentiara Tryasmaya L. A.; Suparmi (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research analyzes elementary school students' learning difficulties through the perspective of Jean Piaget's theory of cognitive development. The main focus of the research is to understand the influence of the concrete operational stage (7–11 years) on students' abilities to process information and solve problems. This research method uses a literature study approach by analyzing relevant journals, books and articles. The research results show that students often have difficulty understanding abstract concepts without the help of teaching aids or experience-based approaches. Factors such as neurological, psychological, and social barriers also play an important role in learning difficulties. This research highlights the importance of implementing concrete, collaborative, experience-based learning strategies and the use of visual aids to support student understanding. Teachers are advised to adapt teaching methods to students' cognitive development stages so that learning is more effective. This article provides practical guidance to help students overcome learning obstacles and reach their maximum potential. These findings also recommend developing a curriculum that supports individual learning styles according to student needs.